2023
DOI: 10.1002/nau.25150
|View full text |Cite
|
Sign up to set email alerts
|

Pelvic floor muscle training: Novel versus traditional remote rehabilitation methods. A systematic review and meta‐analysis on their effectiveness for women with urinary incontinence

Abstract: To investigate the effectiveness of supervised remote rehabilitation programs comprising novel methods of pelvic floor muscle (PFM) training for women with urinary incontinence (UI).Design: A systematic review and meta-analysis including randomized controlled trials (RCTs), involving novel supervised PFM rehabilitation programs as intervention groups (e.g., mobile applications programs, webbased programs, vaginal devices) versus more traditional PFM exercise groups (acting as control); both sets of groups bein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…WBIs have drawn great attention from the medical and hygiene fields due to their advantages of high accessibility and efficiency 17 25 26. Recently, some researchers have attempted to use WBIs to manage UI for women, but the effectiveness of WBIs among this crowd has remained inconclusive,27–31 and even the existing relevant systematic reviews failed to arrive at a consensus on this matter,21–24 32 which impedes clinical decision-making and limits the widespread application of WBIs. Accordingly, this paper presents a protocol for a systematic review and meta-analyses that will summarise the related evidence by systematically reviewing previous RCTs regarding the effectiveness of WBIs in women with UI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…WBIs have drawn great attention from the medical and hygiene fields due to their advantages of high accessibility and efficiency 17 25 26. Recently, some researchers have attempted to use WBIs to manage UI for women, but the effectiveness of WBIs among this crowd has remained inconclusive,27–31 and even the existing relevant systematic reviews failed to arrive at a consensus on this matter,21–24 32 which impedes clinical decision-making and limits the widespread application of WBIs. Accordingly, this paper presents a protocol for a systematic review and meta-analyses that will summarise the related evidence by systematically reviewing previous RCTs regarding the effectiveness of WBIs in women with UI.…”
Section: Discussionmentioning
confidence: 99%
“…Web-based interventions (WBIs), referring to achieving specific health objectives via web-connected devices such as smartphones, computers,and laptops,17 21 might be an effective complement and alternative to narrow the aforementioned gaps and manage women’s UI more effectively through an innovative delivery mode. The benefits of interventions that are delivered via the web include anonymity, relatively low cost and convenience because they enable individuals to receive interventions at anytime and anywhere without face-to-face contact with professionals,22–24 thereby reducing stigma, transportation costs and waiting time for treatments, which are particularly suitable for those with busy schedules or who require flexibility owing to work and family responsibilities. Recent systematic reviews have demonstrated that WBIs can enhance health outcomes among patients with chronic diseases such as diabetes25 and dementia 26…”
Section: Introductionmentioning
confidence: 99%
“…The cerebral cortex and pontine nucleus coordinate the activities of sympathetic and parasympathetic networks with the somatic nervous system through spinal cord conduction tracts. 8 To relieve symptoms of UI, many methods have emerged in past decades, such as physiotherapy, psychological care, manual assistance, behavior therapy, drug therapy, urethral catheterization, and surgical treatment. 1,2 Among those invasive methods, pelvic floor muscle training (PFM) was proven to be effective and recommended as the first option, [3][4][5] and a novel PFM program was launched.…”
Section: Discussionmentioning
confidence: 99%
“…Depending on the severity of their OAB, some participants experienced the effect of the intervention within 2 weeks and up to 3 months or longer. 36 , 37 Therefore, future studies need to consider a longer follow-up period to better measure the effects of PFMT and the fluid moderation intervention. Moreover, to avoid confounding effects, the current study excluded older women who had a urinary tract infection, had more than 100 mL of post-void residual urine, or were taking medication for lower urinary tract symptoms.…”
Section: Discussionmentioning
confidence: 99%